Genetics, crystallization sequence, and age of the South Byron Trio iron meteorites: New insights to carbonaceous chondrite (CC) type parent bodies - Hilton, Connor D. (Geochim Cosmochim Acta, 2019)
The nucleosynthetic Mo, Ru, and W isotopic compositions of the South Byron Trio iron meteorite grouplet (SBT) are consistent with all three meteorites originating on a single parent body that formed in the carbonaceous chondrite (CC) isotopic domain within the Solar nebula. Consistent with a common origin, the highly siderophile element (HSE) concentrations of the SBT can be related to one another by moderate degrees of fractional crystallization of a parental melt with initially chondritic relative abundances of HSE, and with initial S and P contents of ~7 and ~1 wt. %, respectively. Tungsten-182 isotopic data for the SBT indicate the parent body underwent metal-silicate differentiation 2.1 ± 0.8 Myr after calcium aluminum rich inclusion formation, and thermal modeling suggests the parent body formed 1.1 ± 0.5 Myr after CAI formation. This accretion age is not resolved from the accretion ages of other CC and most noncarbonaceous (NC) type iron meteorite parent bodies. Comparison of the projected parental melt composition of the SBT to those projected for the IVA and IVB iron meteorite groups suggests that at least some portions of the CC nebular domain were more oxidized compared to the NC domain. In addition, comparison of the SBT parental melt S content to estimates for parent bodies of the IIAB, IIIAB, IVA, IID, and IVB “magmatic” iron meteorite groups suggests that CC type iron meteorite parental melts were characterized by a general depletion in S, in addition to depletions in some other moderately volatile elements. Based on chemical and O isotope similarities, prior studies have suggested the possibility of a common parent body for the SBT and the Milton pallasite. Molybdenum and Ru isotopic compositions of Milton also provide permissive evidence for this. The HSE concentrations in the Milton metal, however, cannot be related to the SBT by any known crystal-liquid fractionation or mixing path. Thus, Milton more likely formed on a different, chemically distinct, but genetically identical parent body present in the CC nebular domain.